Experimental Investigation of Manufacturing Variables Effect on Electrical Discharge Machining of Titanium Alloy - Enzi Abass; Abdulameer Ahmed Ghazi; Hassoon Omar Hashim; Hamieh Abdallah (Management Systems in Production Engineering)
Titanium alloys are considered one of the materials required in industries. They can be used in various fields due to their high strength and corrosion resistance, but titanium alloys are considered difficult to machine using traditional methods. EDM is used to machine a workpiece using electrical discharges to cut hard materials that are challenging to cut with traditional methods. Therefore, this paper focuses on the machine of a high-strength material-titanium alloy Ti-6Al-4V and studies the influence of cutting process variables on the metal removal rate, tool wear rate, and surface roughness of the samples. The samples matrix form is created depending on the design of experiments method. Pulse-on time, discharge current, and gap process variables with three levels create mathematical models to predict the responses without conducting practical experiments. The results proved that machining variables impacted the responses, which were proven through results data analysis and the interaction plots. Also, the maximum error between experimental and predicted values using the mathematical model was 0.022 (mg/min) for the MRR, 1.719 (mg/min) for the TWR, and 0.334 (μm) for the Ra.